2017
DOI: 10.1002/jmv.24995
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of microRNAs by Japanese Encephalitis virus in human microglial cells

Abstract: JEV infection in CNS leads to the JE neuroinflammation. Children and old age individual have been reported to be more prone to JEV infection. MicroRNAs are endogenous, small non-coding RNAs, which regulate the gene expression. These are ∼22 nucleotide long, conserved RNA sequence that binds at the 3'UTR of a target mRNA and regulate the post-transcriptional gene expression. The role of microRNAs has been reported in several diseases like cancer, viral infection, neuro-degeneration, diabetes etc. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…The target predictions of miRNAs were performed as described earlier . The binding pattern between the target genes and their corresponding miRNAs must follow the Watson‐Crick base‐pairing principle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The target predictions of miRNAs were performed as described earlier . The binding pattern between the target genes and their corresponding miRNAs must follow the Watson‐Crick base‐pairing principle.…”
Section: Resultsmentioning
confidence: 99%
“…The target predictions of miRNAs were performed as described earlier. 24 The binding pattern between the target genes and their corresponding miRNAs must follow the Watson-Crick base-pairing principle. The high false-positive rates of target predictions are the major limitations associated with most of the prediction software.…”
Section: The Target Gene Prediction Of Demsmentioning
confidence: 99%
“…Human microglia, astrocytes, and brain endothelial cells are well‐documented to respond via altered cellular microRNA profile when challenged with viral proteins like HIV‐1 Tat . Another prevalent Flavivirus , Japanese encephalitis virus (JEV) is known to perturb microglial microRNA profiles upon infection . However, contribution of microRNAs in DENV‐induced neuroinflammation is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Another prevalent Flavivirus, Japanese encephalitis virus (JEV) is known to perturb microglial microRNA profiles upon infection. [21][22][23] However, contribution of microRNAs in DENV-induced neuroinflammation is poorly understood. Ubiquitin-proteasome system (UPS) regulates protein turnover in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that microglia can also serve as long-term JEV containers [16]. Although many studies have investigated the molecular mechanisms by which micro RNAs (miRNAs) regulate JEV replication and proliferation [17][18][19][20], the molecular mechanism of the effect of lncRNA on JEV proliferation remains to be explored. Recent studies have shown that lncRNA Malat1 was signi cantly upregulated in JEV-infected mouse Neuro2a cells via the PERK endoplasmic reticulum stress signaling pathway [21], and that silencing lncRNA E52329 and N54010 can regulate the in ammatory response in JEV-infected mouse microglia cells by reducing the phosphorylation levels of JNK and MKK4 [22].…”
mentioning
confidence: 99%